In Vitro Clot Dissolving Activity of Carbomer Based Gel Containing Ethanolic Extract of Calotropis Gigantea Leaves - Alawa, Prerna; Tenguria, Mayank; Nilofey, Vijayshree (Journal of Drug Delivery and Therapeutics, 2018)
Blood clotting is an important and vital process that takes places in humans, animals and birds. At the same time blood clots sometimes considered an issue when developed in the circulatory system due to failure of hemostasis causes vascular blockage and leads to serious consequences in thrombolytic diseases such as acute myocardial or cerebral infarction which may cause death. Certain substances like Alteplase, anistreplase, streptokinase, urokinase, tissue plasminogen activator, Heparin and Aspirin are used as clot dissolving agents. Plants have also been proved to perform such activity. Calotropis gigantea L. is a traditional medicinal plant with several pharmacological properties belongs to the family Apocyanaceae of Asclepiadaceous was investigated for its efficacy for blood clot dissolving activity under in vitro conditions when incorporated into carbomer based gels. The ethanolic extract of the leaves of C. gigantea was prepare by soxhlation which upon analysis reported to contain alkaloids, glycosides, flavonoids, tannins, terpenoids and saponins as usual components as were reported in earlier investigations. There were 3 gels with ethanolic leaf extract C. gigantea with 1 mg, 0.5 mg and 0.25 mg per gram of 1% Carbopol-940 gel containing methyl paraben, glycerol and water. The two gels containing sterile distilled water and 0.1 mg per gram gel streptokinase enzyme served as –ve and positive controls respectively. The in vitro thrombolytic of clot dissolving activity war performed on goat blood collected from slaughter houses. From the results the percentage clot dissolving activity of gels containing 1 mg, 0.5 mg and 0.25 mg C. gigantea extract per gram were reported as 34%, 27% and 14% respectively considered significant when compared to the activity of standard streptokinase in the gel. The activity of these experimental gels describes the possibility of development of new safe, and non reactive topical anti-clot gel products using herbal or plant components like C. gigantea extracts.Keywords: Calotropis gigantea L, Streptokinase, Thrombolytic activity, Carbopol gel, Biopharmaceutical.